An exploration of the relationship between adverse events on the farm and suicidal ideation in farmers. (December 2022) - Phalp, Laura; Corcoran, Rhiannon; Eames, Catrin; Naik, Aarun
Background: The risk of suicide for agricultural workers in parts of the United Kingdom (UK) is almost twice the national average. Existing literature has suggested that adverse farming events, where failure is determined by uncontrollable and unpredictable forces, may be to blame. Yet, the impact of such events on farmer suicidality has not been explicitly explored. Aims: The present paper therefore aimed to investigate the relationship between adverse farming events and suicidal ideation in farmers. Methods: A cross-sectional questionnaire battery was disseminated between July 2018 and February 2019, and completed by 170 adult farmers. Results: Over a 12-month period, 88.8% reported that they had experienced an adverse farming event and 32.9% said that they had experienced suicidal thoughts. Correlational analysis revealed a relationship between these variables. Conclusions: The high prevalence of suicidal ideation within farmers demonstrates a critical need for intervention. Likewise, the prevalence of adverse farming events suggests that interventions need to be appropriately tailored, with greater understanding about the impact of such events on the mental wellbeing of farmers.